From the ground up: Impacts of a pro-poor community-driven development project in Nigeria - Nkonya, Ephraim M.; Phillip, Dayo; Mogues, Tewodaj; Pender, John L.; Yahaya, Muhammed Kuta; Adebowale, Gbenga; Arokoyo, Tunji; Kato, Edward (International Food Policy Research Institute, 2008)
The community-driven development (CDD) approach has become increasingly popular because of its potential to develop projects that are sustainable, are responsive to local priorities, empower local communities, and more effectively target poor and vulnerable groups. The purpose of this study is to assess the impacts of Fadama II, which is a CDD project and the largest agricultural project in Nigeria. This study used propensity score matching (PSM) to select 1728 comparable project beneficiaries and non-beneficiaries. The study also used double difference methods to compare the impact indicators. Our results show that Fadama II project succeeded in targeting the poor and women farmers in its productive asset acquisition component. Participation in the project also increased the income of beneficiaries by about 60 percent, which is well above the targeted increase of only 20 percent in the six year period of the project. Regarding rural infrastructure investments, we found that the Fadama II project had positive near-term impacts on beneficiaries? access to markets and transportation costs, although the study revealed surprising effects on beneficiaries? commercial behavior and statistically insignificant impacts on nonfarm activities. We also observed that Fadama II increased the demand for postharvest handling technologies but did not have a significant impact on the demand for financial management and market information. Fadama II reduced the demand for soil fertility management technologies. The decline likely reflects the project?s focus on providing postproduction advisory services and suggests the need for the project to increase its support for soil fertility management and thus limit the potential for land degradation resulting from increased agricultural productivity. Overall, the Fadama II project has achieved its goal of increasing the incomes of the beneficiaries in the first year of its operation. The project has also succeeded in targeting the poor and vulnerable in its productive-asset component, even though that did not appear to increase significantly short-term household incomes among the poorest asset tercile. The unique feature that could have contributed to the significant impact of the project in a short time is its broad-based approach, which addresses the major constraints limiting the success of CDD projects that address only one or two constraints. This has implications on planning poverty reduction efforts in low-income countries. Given that the poor face numerous constraints, a CDD project that simultaneously addresses many constraints will likely build synergies that will lead to larger impacts than will a project that addresses only one or two constraints. This suggests the need for the government and donors to pool resources and initiate multipronged CDD projects rather than many isolated projects.--Author's Abstract